Problem of comorbidity in patients with bronchial asthma - D. V. Ushakova; E. L. Nikonov (Лечащий Врач)
Prevalence of allergic rhinitis, chronic obstructive pulmonary disease, gastroesophageal reflux disease, arterial hypertension, chronic ischemic heart disease, diabetes mellitus and oncologic diseases was studied in patients with bronchial asthma.